Oral Mycobiome Differences in Various Spatial Niches With and Without Severe Early Childhood Caries - Cui, Yuqi; Wang, Yinuo; Zhang, Yuwen; Pang, Liangyue; Zhou, Yan; Lin, Huancai; Tao, Ye (Frontiers in Pediatrics, 2021)
Purpose: Severe early childhood caries (S-ECC) is a microbe-mediated disease with tooth hard tissue destruction. However, the role of the fungal community in various ecological niches of deciduous dental caries has not been fully elucidated. This study aimed to analyze the differences of mycobiome in diverse spatial niches with and without S-ECC. Method: A total of 48 samples were obtained from 8 S-ECC children (SE group) and 8 caries-free children (CF group) aged 4–5 years. Unstimulated saliva (S), healthy supragingival plaque (FMIX), mixed plaque from decayed teeth (SMIX) and carious lesion (DMIX) samples were collected. The ITS2 region of the fungi was amplified and sequenced using the Ion S5™XL platform. Results: A total of 281 species were identified. Candida albicans showed relatively higher abundance in S-ECC children, while Alternaria alternata and Bipolaris sorokiniana were more enriched in CF group. In this study, the relative abundance of C. albicans in CF.FMIX (0.4%), SE.FMIX (12.5%), SE.SMIX (24.0%), and SE.DMIX (37.2%) increased successively. Significant differences of fungal species richness and diversity were observed between SE.FMIX-SE.SMIX, SE.FMIX-SE.DMIX (P < 0.05). Conclusions: The diversity of fungal communities in S-ECC children showed significant differences in various spatial niches of primary teeth. The richness of C. albicans was closely related to the caries states and depth, suggesting that it may play a crucial role in caries pathogenicity.